PEREMPUAN DALAM SWARA SESTRA DAN FAKTA PERKAWINAN ENDOGAMI ARISTROKAT JAWA - Fajar Wijanarko (Badan Pengembangan dan Pembinaan Bahasa, 2018)
Abstract: In general, Javanese women are well-imagery and often raised as a form of teaching in literature. However, in the Swara Sěstra text, it is actually metaphorically as a senthe leaves, the allegory of young women who being a co-wife to older women. This issue becomes complicated when the situation occurs in the aristocratic environment of Java. By the discipline of philology with methods of text editing and translation, the phenomenon of women in the text of Swara Sěstra will be expressed. The semiotic study of text through heuristic and hermeneutical readings then becomes an attempt at interpreting the text. At the end of the discussion, it is known that female allegory as a senthe refers to the image of poor Javanese women. Behind the meaning of the text is then found also evidence that this female allegedly dragged historical facts about the rampant endogamy marriage in the nobility. Even the behavior repeatedly happen, especially in the inner court environment.Abstrak: Pada umumnya, perempuan Jawa bercitra baik sehingga kerap dimunculkan sebagai bentuk ajaran dalam sastra. Akan tetapi, dalam teks Swara Sěstra justru dimetaforakan sebagai daun senthe, yaitu alegori perempuan muda yang dimadu dengan perempuan yang lebih tua. Persoalan ini menjadi rumit ketika keadaan tersebut terjadi di lingkungan aristokrat Jawa. Berbekal disiplin filologi dengan metode penyuntingan teks dan penerjemahan, fenomena perempuan dalam teks Swara Sěstra akan diungkapkan. Telaah teks secara semiotik melalui pembacaan heuristik dan hermeneutik kemudian menjadi upaya dalam menafsirkan teks. Pada akhir pembahasan, diketahui bahwa alegori perempuan sebagai senthe merujuk pada citra perempuan Jawa yang tidak baik. Di balik pemaknaan teks tersebut kemudian ditemukan pula bukti bahwa pengalegorian perempuan ini menyeret fakta sejarah tentang maraknya perkawinan endogami di lingkungan bangsawan. Bahkan perilaku tersebut merupakan hal yang subur, terutama di lingkungan dalam tembok istana.